Sirindhornia Pinkaew and Muadsub (Lepidoptera: Tortricidae), a new enarmoniine genus from Thailand - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2014)
A new enarmoniine genus, Sirindhornia, n. gen., is described based on the type species, Sirindhornia pulchella, n. sp., and three additional new species: Sirindhornia chaipattana, n. sp., Sirindhornia curvicosta, n. sp., and Sirindhornia bifida, n. sp., all from Thailand. A fifth species represented only by a single female is morphologically characterized but not formally described. Sirindhornia is most closely related to Anthozela Meyrick and Irianassa Meyrick but is easily distinguished by unique appendages of the tegumen and a conspicuous henion in the male genitalia.